Cover Image, Volume 28, Issue 6. Issue 6 (June 2018) - Ostroff, Linnaea E.; Watson, Deborah J.; Cao, Guan; Parker, Patrick H.; Smith, Heather; Harris, Kristen M.
Abstract : Cover legend: This cover image, by Linnaea Ostroff et al., is based on the Research Article Shifting patterns of polyribosome accumulation at synapses over the course of hippocampal long‐term potentiation, DOI:10.1002/hipo.22841 .